Perhitungan Daya Kompresor dan Beban Kalor Pada Hasil Tangkapan Ikan Laut - Ziliwu, Boby Wisely; Aprilio Muharram, Darel (Infotekmesin, 2023)
A refrigeration machine is needed on a fishing boat because the purpose of catching is to catch as many fish as possible and maintain the quality of the catch. In general, fishing vessels use mechanical refrigeration machines in an effort to maintain the quality of the catch up to the hands of consumers. The results of checking products that enter the hold showed the average initial temperature of the fish entering the hold was 11,7 oC. The final temperature of fish products after going through the freezing process is 2,075 oC. The total product load calculation is 101,1 KW and the average product heat load on the hold is 9,1 KJ/s. By knowing the suction pressure, exhaust, and working temperature of the compressor through a worksheet that is journalized every day, as well as the temperature in the pipe after the condenser, and the expansion valve using the Mollier R-22 diagram and the Saturation Properties-Temperature R-22 table, it is known that the average compressor power average of 1,9 KW and actual COP averaging is 4,6 KJ/Kg. The total compressor power result calculation is 20,96 KW with an average usage of 1,9 KW. The total result of the COP actual calculation is 51,4 with an average of 4,6.